Injuries and deaths proximate to oleoresin capsicum spray deployment: A literature review. (June 2021) - Semple, Tori; Jenkins, Bryce; Bennell, Craig
This literature review assessed research related to injuries and deaths proximate to oleoresin capsicum (OC) spray deployment. Our review of 22 relevant documents suggests that OC spray is often effective and is typically associated with decreased odds of both subject and "deployer" injury. When OC-associated injuries do occur, they consistently appear to be relatively minor. When OC spray is used proximate to a subject's death, common themes are present. Given the limitations of the research in this area, one must be cautious when speaking to the nature of the relationship between OC spray and injuries or deaths.